Careers in cities: An interdisciplinary space for advancing the contextual turn in career studies - Tams S; Kennedy JC; Arthur MB; Chan KY (SAGE Publications on behalf of the Tavistock Institute, 2021)
With careers increasingly taking place within and between cities, this article maps the territory for research and theory on careers in cities. Cities present a microcosm for advancing a systemic understanding of people’s careers over time and in relation to broader issues. We acknowledge cities’ multilayered contexts by identifying six spheres—locality and networks, material infrastructure, economic activities, non-work, virtual reconfiguration, and nexus of social change. The interplay between careers and these city spheres informs intertwined phenomena such as well-being, mobility, and migration. To guide further research, our framework distinguishes two meta-theoretical perspectives. An entity perspective examines causal relationships across levels, analyzing how urban characteristics explain career-related phenomena, and vice versa. A constructionist perspective examines how people’s construal of careers in cities draws on cultural repertoires about work, non-work life, and the city, including its social, symbolic, and material aspects. We use the framework to discuss contributions of the five articles of this special issue. A career lens can contribute to our understanding of cities being sources of both stability and change. With cities currently facing significant disruptions, there has never been a more appropriate time for careers researchers to incorporate the city as context.
CAUL read and publish agreement 2023
Keywords: careers; cities; economic development; migration; quality of life; urban policymaking; 1503 Business and Management; 1608 Sociology; 1701 Psychology